Pengembangan Pengembangan LKPD Berbasis Project-Based Learning Berorientasi STEM pada Materi Gambar Teknik Arsitektur 2D untuk Siswa Kelas XI SMK - Afrizal Reynaldi; Imam Alfianto; Muhammad Aris Ichwanto; Fadila Fitria Wulandari (Jurnal Pensil : Pendidikan Teknik Sipil, 2026)
There has to be a steady supply of skilled workers, particularly in the field of vocational education, if science and technology are to keep up with the current rate of advancement. Limited learning facilities and an inadequate teaching staff are only two of the many problems that vocational education in Indonesia continues to confront. The purpose of this research is to use the Project-Based Learning (PjBL) approach to create STEM-focused Student Worksheets for the Building Information and Modeling Design (DPIB) course at technical institutions, with a focus on two-dimensional (2D) architectural drawing. Analysis, design, development, implementation, and evaluation are the steps that make up the ADDIE development model, which was used as the research technique in this study. Thirty students from the eleventh grade at SMK Negeri 11 Malang participated in the study. Questionnaires on students' learning requirements, validation sheets from experts, and readability exams administered to students were all used to gather data. Descriptive quantitative methods were used for data analysis. With an average expert validation score of 90.20% and a student readability score of 88.34%, the created worksheets were deemed extremely valid and intelligible, according to the findings. These results show that the worksheets improve students' knowledge and abilities in architectural drawing as measured by industry standards. Thus, STEM-focused PjBL-based worksheets constitute a viable and efficient medium for vocational education instruction.